Elaboration of cookies with pineapple peel flour from passion fruit (Passiflora edulis) enriched with anchovy protein concentrate (Engraulis ringens) - Avalos-Ramírez, Yosef (2024)
Fruit waste has multiple uses in the food industry, such as in the production of flour from pineapple, pitahaya or passion fruit peels. In turn, it will be proven that these foods offer a valuable nutritional contribution to the body. In recent times, there has been notable progress in the food industry, with a growing focus on creating innovative and sustainable products. In this context, the research focused on the preparation of cookies where unconventional ingredients are used, such as passion fruit, which are characterized by their richness in bioactive and antioxidant compounds. Likewise, their optimal formulation was found using 95 % flour. wheat, 3 % shell flour and 2 % hydrolyzed anchovy protein concentrate. A particularly interesting aspect of the study was the incorporation of hydrolyzed anchovy protein concentrate, a rich source of protein and omega-3. In addition, a physical sensory analysis was carried out resulting in satisfactory acceptance, it will be obtained that these cookies offer a significant contribution of nutrients beneficial to health.